HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KECEMASAN PASIEN ANAK RAWAT INAP DI RUMAH SAKIT CANDIMAS MEDICAL CENTER KOTABUMI KABUPATEN LAMPUNG UTARA - Linawati Novikasari; Hairunisa Hairunisa (Universitas Malahayati Lampung, 2020)
ABSTRACT : THE CORRELATION BETWEEN CARING BEHAVIOR OF NURSES AND ANXIETY LEVEL ON PEDIATRIC INPATIENTS AT CANDIMAS MEDICAL CENTER HOSPITAL OF KOTABUMI OF LAMPUNG UTARA REGENCY Introduction: Based on pre-survey data conducted through interview and observation on 10 January 2019 at Pediatric Wards of Candimas Medical Center Hospital of Kotabumi, there were ten children. Seven out of ten children (70%) experienced worries while the rest three children (30%) was not worrying. Based on the interview on ten companions of the children, seven of them (70%) stated the nurses in charge did not exhibit caring behavior meanwhile three others (30%) stated the nurses performed caring conducts. On another pre-survey site, Hi M. Yusuf Hospital of Kotabumi of Lampung Utara Regency, there were four out of ten children (40%) got anxiety while the rest six (60%) did not get anxiety. On the family point of view, there were four uncaring nurses (40%) but other six nurses (60%) had caring performance. By comparing the data, it is known that the anxiety at Candimas Medical Center Hospital of Kotabumi had more anxious children than Hi. M. Yusuf Hospital did.Objective: this study was to identify the correlation between caring behavior of nurses and anxiety level on pediatric inpatients at Candimas Medical Center Hospital of Kotabumi of Lampung Utara Regency in 2019.Method: this was a quantitative study with cross sectional approach. the population comprised 36 parents who accompanied their children at the pediatric wards. The sampling technique was total sampling for 36 respondents.Result: the analysis revealed that 13 nurses performed a good caring while three patients (30.8%) experienced anxiety. On the other hand, 26 nurses conducted a good caring while six patients (26.1%) were not anxious (P value 0.030 and OR 0.157).Conclusion: There was a correlation between caring behavior of nurses and anxiety level on pediatric inpatients at Candimas Medical Center Hospital of Kotabumi of Lampung Utara Regency in 2019. The nurses at the hospital are suggested to improve their caring quality in handling pediatric inpatients by giving counseling about disease information to the patients. Keywords : caring behavior and anxiety ABSTRAK : HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KECEMASAN PASIEN ANAK RAWAT INAP DI RUMAH SAKIT CANDIMAS MEDICAL CENTER KOTABUMI KABUPATEN LAMPUNG UTARA Pendahuluan :Berdasarkan data prasurvey dengan metode wawancara dan observasi pada tanggal 10 Januari 2019 Di Ruang Anak Rumah Sakit Candimas Medical Center Kotabumi, terdapat 10 pasien anak yang dirawat di ruang anak, dari 10 responden 7 anak (70%) mengalami kecemasan dan 3 anak (30%) tidak cemas, sedangkan dari hasil wawancarapadakeluargapasienmengatakanterdapat 10 perawat, dimana 7 perawat (70%)tidak caring dan 3 perawat (30%) caring, dari 10 responden 4 anak (40%) mengalamikecemasan dan 6 anak (60%) tidak cemas, sedangkan terdapat 10 perawat, dimana 4 perawat (40%) tidak caring, maka angka kejadian kecemasan anak yang disebabkan oleh kecemasan lebih tinggi Di Rumah Sakit Candimas Medical Center Kotabumi dari pada RS Hi M.Yusuf KotabumiTujuan :Untuk mengetahui hubungan perilaku caring perawat dengan tingkat kecemasan pasien anak rawat inap di Rumah Sakit Candimas Medical Center Kotabumi Lampung Utara tahun 2019Metode :Jenis penelitian kuantitatif rancangan analitik pendekatan cross sectional. Populasi orang tua anak rawat inap pada ruang anak berjumlah 36 responden dengan sampel 36 responden. Teknik sampling Total SamplingHasil : hasil penelitian 13 perawat perilaku caring baik dimana 4 pasien (30,8%) mengalami cemas, 23 perawat perilaku caring baik 6 pasien (26,1%) tidak cemas dan (p-value 0,030 dan OR 2,310).Kesimpulan : Ada hubungan antara perilaku caring perawat dengan kecemasan pasien anak rawat inap Di Rumah Sakit Candimas Medical Center Kotabumi Lampung Utara Tahun 2019. Diharapkan para tenaga kesehatan dapat meningkatkan mutu pelayanan kesehatan secara aktif dalam memberikan penyuluhan kesehatan khususnya tentang pengetahuan peyakit yang dialami pasien.Kata Kunci : Perilaku Caring Kecemasan